2020
DOI: 10.1016/j.heliyon.2020.e05449
|View full text |Cite
|
Sign up to set email alerts
|

Public policies and tax evasion: evidence from SAARC countries

Abstract: In compliance with the socioeconomic theory, the study has strived to investigate the impact of economic and non-economic public policies on tax evasion using panel data of 7 SAARC countries covering the period from 1998 to 2015. The study has applied the ordinary least square with fixed effect and random effect models to analyze the data assembled. The result of the study implies that the higher the degree of economic freedoms, the lower the tax evasion. More specifically, the government policies about proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 49 publications
2
31
1
Order By: Relevance
“…Torgler (2006) found that religious faith substantially impacts the taxpayers' tax morale behavior; it ultimately shapes the taxpayers' compliance behavior. Nurunnabi (2018) and Islam et al (2020) found religiosity as the most crucial factor that negatively influences TE. There is limited research on the effect of governance quality and religiosity on TE in OECD countries.…”
Section: Q2mentioning
confidence: 98%
See 3 more Smart Citations
“…Torgler (2006) found that religious faith substantially impacts the taxpayers' tax morale behavior; it ultimately shapes the taxpayers' compliance behavior. Nurunnabi (2018) and Islam et al (2020) found religiosity as the most crucial factor that negatively influences TE. There is limited research on the effect of governance quality and religiosity on TE in OECD countries.…”
Section: Q2mentioning
confidence: 98%
“…Several factors of socioinstitutional norms have been identified in prior research, which has effects on TE (Nurunnabi, 2018). Governance qualities (Umar et al, 2019;Yamen et al, 2018) and religiosity (Islam et al, 2020;Nurunnabi, 2018) may affect the tax behavior of society in particular. Nurunnabi (2018) identified three major playersthe state, the tax authority, and taxpayersin the tax social network within which they interact among themselves, which in turn affects TE.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…All these questions concern the problems faced by the institutions that make decisions regarding content, the procedures determined, the strategy, the timing of the decisions, and the implementation besides the conclusion about the definition of the policy as meant. At present, the term policy is more frequently and widely used concerning government actions and state behavior in general (Hardy et al, 2020;Islam et al, 2020). The policy is a tool or instrument to regulate the population from top to bottom.…”
Section: Introductionmentioning
confidence: 99%